Strengthening of lateral activation in adult rat visual cortex after retinal lesions captured with voltage-sensitive dye imaging in vivo - Palagina, Ganna; Eysel, Ulf T; Jancke, Dirk (Proceedings of the National Academy of Sciences - PNAS, 2009)
Sensory deprivation caused by peripheral injury can trigger functional cortical reorganization across the initially silenced cortical area. It is proposed that intracortical connectivity enables recovery of function within such a lesion projection zone (LPZ), thus substituting lost subcortical input. Here, we investigated retinal lesion-induced changes in the function of lateral connections in the primary visual cortex of the adult rat. Using voltage-sensitive dye recordings, we visualized in millisecond-time resolution spreading synaptic activity across the LPZ. Shortly after lesion, the majority of neurons within the LPZ were subthresholdly activated by delayed propagation of activity that originated from unaffected cortical regions. With longer recovery time, latencies within the LPZ gradually decreased, and activation reached suprathreshold levels. Targeted electrode recordings confirmed that receptive fields of intra-LPZ neurons were displaced to the retinal lesion border while displaying normal orientation and direction selectivity. These results corroborate the view that cortical horizontal connections have a central role in functional reorganization, as revealed here by progressive facilitation of synaptic activity and the traveling wave of excitation that propagates horizontally into the deprived cortical region.